2021
DOI: 10.3390/md19020065
|View full text |Cite
|
Sign up to set email alerts
|

Two New Phomaligols from the Marine-Derived Fungus Aspergillus flocculosus and Their Anti-Neuroinflammatory Activity in BV-2 Microglial Cells

Abstract: Two new phomaligols, deketo-phomaligol A (1) and phomaligol E (2), together with six known compounds (3–8) were isolated from the culture broth of the marine-derived fungus Aspergillus flocculosus. Compound 1 was first isolated as a phomaligol derivative possessing a five-membered ring. The structures and absolute configurations of the new phomaligols were determined by detailed analyses of mass spectrometry (MS), nuclear magnetic resonance (NMR) data, optical rotation values and electronic circular dichroism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The revised structure of ring B is closely similar to that of sarcosone derivatives, which are common fungal polyketides containing a 3-methoxycyclohexenone ring as a substructure, and we have isolated several 3-methoxycyclohexenone analogues from the same strain. , Therefore, we compared the chemical shifts of the revised structure of ring B and 3-methoxycyclohexenone derivatives and found that they are well matched to each other (Figure S19). Moreover, the UV spectrum of 1 (Figure S27) displayed a strong absorption peak at 256 nm, which was similar to that of other 3-methoxycyclohexenones, and the IR spectrum (Figure S28) showed an absorption band at 1643 cm –1 corresponding to an α,β-conjugated carbonyl as in the revised structure (unconjugated carbonyl as in the proposed structure absorbs at >1700 cm –1 ). , Additionally, an extensive literature review revealed that the chemical shift of the methyl group in methyl esters of glucuronic acid (similar to the proposed structure) is smaller than 53 ppm (δ C 51–53) (Table S2).…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…The revised structure of ring B is closely similar to that of sarcosone derivatives, which are common fungal polyketides containing a 3-methoxycyclohexenone ring as a substructure, and we have isolated several 3-methoxycyclohexenone analogues from the same strain. , Therefore, we compared the chemical shifts of the revised structure of ring B and 3-methoxycyclohexenone derivatives and found that they are well matched to each other (Figure S19). Moreover, the UV spectrum of 1 (Figure S27) displayed a strong absorption peak at 256 nm, which was similar to that of other 3-methoxycyclohexenones, and the IR spectrum (Figure S28) showed an absorption band at 1643 cm –1 corresponding to an α,β-conjugated carbonyl as in the revised structure (unconjugated carbonyl as in the proposed structure absorbs at >1700 cm –1 ). , Additionally, an extensive literature review revealed that the chemical shift of the methyl group in methyl esters of glucuronic acid (similar to the proposed structure) is smaller than 53 ppm (δ C 51–53) (Table S2).…”
mentioning
confidence: 66%
“…During the course of our ongoing research for novel marine natural products, we have isolated a number of oxygenated cyclohexenone derivatives from two strains of Aspergillus flocculosus , 01NT-1.1.5 and 168ST-16.1. Among them, compound 1 was isolated as a pure compound with identical 1D and 2D NMR data to those of asperspiropene A. However, the HRESIMS data of 1 were different from the previously published data for asperspiropene A. Additionally, we found that some 2D NMR data of asperspiropene A (COSY and HMBC) were incorrectly interpreted .…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Culture broth from marine-derived fungus, Aspergillus flocculosus , produced two new compounds, phomaligol E ( 15 ), and deketo-phomaligol A ( 17 ). 9 Our analysis showed that phomaligol E ( 15 ), needs revision to 4-epimer ( 16 ), while deketo-phomaligol A ( 17 ) required a more extensive revision into α,β-unsaturated cyclopentanone 18 .…”
mentioning
confidence: 84%